2022
DOI: 10.2147/ijgm.s370956
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Its Associated Risk Factors Among Patients with Rheumatoid Arthritis in the Kingdom of Saudi Arabia

Abstract: Data regarding hypertension prevalence among patients with rheumatoid arthritis in Saudi Arabia are scarce. This study was aimed at estimating the prevalence of hypertension and its associated risk factors among patients with rheumatoid arthritis in Saudi Arabia. Patients and Methods: This was a cross-sectional study of adult patients with rheumatoid arthritis who presented at the OPD of two major hospitals in Riyadh city. Patient information such as demographic characteristics, comorbidities, drug use, and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Our study provides strong evidence supporting the relationship between pre-hypertension and hypertension, which is consistent with ndings from other studies (55-58). Many cross-sectional studies have reported hypertension as a risk factor for rheumatoid disease (59,60). Whether it is a risk factor for rheumatoid disease or not requires more longitudinal studies.…”
Section: The Association Between the Clinical Variables With Incidenc...mentioning
confidence: 99%
“…Our study provides strong evidence supporting the relationship between pre-hypertension and hypertension, which is consistent with ndings from other studies (55-58). Many cross-sectional studies have reported hypertension as a risk factor for rheumatoid disease (59,60). Whether it is a risk factor for rheumatoid disease or not requires more longitudinal studies.…”
Section: The Association Between the Clinical Variables With Incidenc...mentioning
confidence: 99%